ASUHAN KEBIDANAN REMAJA PADA NN “E” DENGAN DISMENOREA PRIMER DI RUMAH SAKIT UMUM BAHAGIA MAKASSAR - Nurfadillah; Firdayanti; Nadyah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction During menstruation, almost all women have experienced discomfort such as the cramping pain in the lower abdomen accompanied by nausea, dizziness, and even fainting. Dysmenorrhea is a physical disorder in women occurring just before or during menstruation characterised by cramping pain, in the absence of other diseases such as endometriosis. Primary dysmenorrhea is menstrual pain that occurs without any anatomical abnormalities of the genitals. The prevalence rates of this disease are high, and the initial presentation of primary dysmenorrhea typically occurs in adolescence. Method The research was conductedbased on the authority of midwives by utilizing the 7-stages of Varney management approach. Result The results of this study indicated that there were no serious obstacles found during the conduct of primariy dysmenorrhea care and treatment to Ms. “E”. The patient was advised to have an adequate rest and to do regular and aerobic exercises so that her menstrual pain and her primary dysmenorrhea could be reduced. After the treatment, care, and regular monitoring process, it was evident from this research that the menstrual blood and pain of the patient was reduced. Conclusion Based on the 7-stages of Varney management approach and SOAP documentation procedure used in this research, it could be concluded that the condition of the patient was normal in which no complications were found. After the treatment, there were no more pain felt by the patient, and all the vital signs of the patient were within normal. In this case, the medical staff and midwives play an important role in the success of the care and treatment to the patient.